A review of research methods for accounting urban green space carbon sinks and exploration of new approaches - Dong, Lili; Wang, Yiquan; Ai, Lijiao; Cheng, Xiang; Luo, Yu (Frontiers in Environmental Science, 2024)
Along with urbanization and industrialization, carbon emissions have been increasing significantly, resulting in global warming. Green space has been widely accepted as a natural element in cities to directly increases carbon sinks and indirectly reduces carbon emissions. The quantification of carbon benefits generated by green space is an important topic. This paper aims to provide a comprehensive review of the methods for measuring carbon sinks of green spaces. The results indicate that existing assessment methods can accurately estimate the carbon sinks in green spaces at large scales. However, existing methods are not fully applicable to studies of urban green spaces, due to the low precision of research results. The assimilation method is the most suitable method to study the carbon sequestration efficiency of plants and can project the carbon sinks of urban green spaces at large scales through macroscopic means. Even though, the results of assimilation experiments are unstable under different weather conditions. To address existing research challenges, this paper proposes a photosynthetic rate estimation method based on the light-response curve which is an efficient method to describe the relationship between light intensity and net photosynthetic rate in studying plant physiological characteristics. The newly proposed method, through integrating net photosynthesis-light response curves and urban light intensity associated with meteorological data, has advantages of short measurement time and ensuring standardized experimental environment for result comparability. Overall, this study is important to combine meteorology and plant physiology to propose a photosynthetic rate estimation method for optimizing carbon sink measurement in urban green spaces. The method is more convenient for application for its simple experimental process and result comparability . In practice, this study provides guidance for low-carbon urban green space planning and design, and helps to promote energy conservation and emission reduction through nature-based solutions.